2002
DOI: 10.1590/s0100-73862002000100006
|View full text |Cite
|
Sign up to set email alerts
|

Flows of Bingham Materials Through Ideal Porous Media: an Experimental and Theoretical Study

Abstract: The flow of Bingham liquids through porous media has been studied. Experiments have been performed to determine the flow rate / pressure drop relationship for the flow of a grease of Binghamian rheological behavior through an array of rods of circular cross section. The yield stress and plastic viscosity of the grease have been determined with the aid of a controlled stress rotational rheometer. To investigate a wider range of the flow parameters, the mass and momentum conservation equations have been solved n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A commonly used but more complicated alternative is the Buckingham-Reiner model (see Buckingham [8], Mendes et al [9] and Balhoff and Thompson [10]) which is given by,…”
Section: Governing Equationsmentioning
confidence: 99%
“…A commonly used but more complicated alternative is the Buckingham-Reiner model (see Buckingham [8], Mendes et al [9] and Balhoff and Thompson [10]) which is given by,…”
Section: Governing Equationsmentioning
confidence: 99%
“…A similar procedure will be used in §3 for plane channels. This model has been adopted by many authors including Balhoff and Thompson (2004) and Mendes et al (2002).…”
Section: Flows Of Bingham Fluids In Porous Mediamentioning
confidence: 99%
“…Of particular importance in this area is the work carried out by Wu et al (1992). They modified the Darcy's law for Bingham fluids in such a way that it incorporates a minimum pressure gradient which is proportional to the fluid's yield stress (Mendes et al, 2002;Zhang et al, 2014). Using the idea of minimum pressure gradient, they studied the displacement of Bingham fluids in the one-dimensional Buckley-Leverett problem and showed that there exists an ultimate displacement saturationwhich depends on the oil's yield stressbeyond which the sweep efficiency does not improve no matter how long the displacement operation is continued.…”
Section: Introductionmentioning
confidence: 99%